The quality of the Internet Business Reporting (IBR) practices : empirical evidence from five countries / Siti Rosmaini Mohd. Hanafi - Mohd. Hanafi, Siti Rosmaini (2010)
The present research was initiated based on the need to understand the nature and diversity of the Internet Business Reporting (IBR) practices among the companies in the developed (i.e., USA, UK and Singapore) and developing countries (i.e., Thailand and Malaysia). The primary research objectives were: 1) to develop a measurement of the quality of the IBR practices; 2) to analyse and compare the quality of the IBR practices; 3) to analyse the trends of the quality of the IBR practices; 4) to investigate and analyse the stages of the IBR practices; and 5) to examine the relationship between the various predictors of the IBR practices and the quality of the practices. Detailed steps and approaches were undertaken in designing the research. Although the primary data collection was through the assessment of the individual corporate website, other data collection approaches such as the use of a questionnaire survey was also conducted aimed to substantiate the primary data collection process. The present study also applied a multi-theoretical approach to provide better explanation on the hypothesised relationships between each variable. The present study employed the agency, signaling and proprietary cost theories. The results justify the appropriateness of using these theories. Furthermore, an index was developed to measure the quality of the IBR practices known as the Internet Business Reporting Quality (IBRQ). Statistical analysis was performed using the Stepwise Multiple Regression and Hierarchical Multiple Regression. The results supported most of the hypotheses and substantiated the existing studies on the variation in the IBR practices among the companies in five countries. The quality of the IBR practices was found to differ significantly among the companies in the developed and developing countries. The companies in the developed countries were found to be in Stage 2 while their counterparts in the developing countries were mostly in Stage 1 in the IBR practices. Furthermore, the results also supported that the industry classification was the significant predictor towards the IBR practices. Nonetheless, it indicated less moderating effect to improve the predictive ability between the predictors and the quality of the IBR practices.